1993
DOI: 10.1002/ajmg.1320460312
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and behavioral profile of the oculocerebrorenal syndrome of Lowe

Abstract: The diagnosis of OCRL is compatible with normal intelligence. Maladaptive behaviors significantly interfere with adaptive functions. These behaviors appear to define a characteristic behavioral phenotype in OCRL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 29 publications
(16 reference statements)
2
40
0
Order By: Relevance
“…Descriptions of additional infants with similar features led to the identification of the cardinal features of the syndrome: congenital cataracts, Fanconi syndrome of the proximal renal tubules, and mental retardation inherited as an X-linked trait (2). OCRL is a rare disease with only a few hundred known patients in the United States (3).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Descriptions of additional infants with similar features led to the identification of the cardinal features of the syndrome: congenital cataracts, Fanconi syndrome of the proximal renal tubules, and mental retardation inherited as an X-linked trait (2). OCRL is a rare disease with only a few hundred known patients in the United States (3).…”
Section: Introductionmentioning
confidence: 99%
“…Mean IQ is in the moderate range (40 Ͻ IQ Ͻ 54) although 25% of patients score above and 25% below this interval (3,6). Neonatal and infantile hypotonia of central nervous system origin is also a frequent feature but improves or disappears with age (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that OCRL1 mutations lead to a Dentlike phenotype, Dent-2 disease, which manifests mild developmental delays and visually insignificant peripheral cataracts (Hoopes et al 2005: Bökenkamp et al 2009). Kenworthy et al (1993) reported that 47 males with Lowe syndrome had a mean IQ of 45-54, characteristic of moderate mental impairment, and that the IQs of 25% were within the normal range (>70). Further, >80% exhibited maladaptive behavior, particularly stubbornness, temper tantrums, and other stereotypic behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients show behavioral disturbances, irritability, outbursts of anger, and stereotypic behavior (Kenworthy et al 1993). Therefore, the severity of the developmental disorder may remain mild in patients with the missense mutations.…”
Section: Discussionmentioning
confidence: 99%